2013
DOI: 10.1002/j.2161-1882.2013.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐Generation Undergraduate Students' Social Support, Depression, and Life Satisfaction

Abstract: First-generation undergraduate students face challenging cross-socioeconomic cultural transitions into college life. The authors compared first-and non-first-generation undergraduate students' social support, posttraumatic stress, depression symptoms, and life satisfaction. First-generation participants reported less social support from family and friends, more single-event traumatic stress, less life satisfaction, and marginally more depression symptomatology than non-first-generation participants, but signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 27 publications
4
133
1
4
Order By: Relevance
“…It can be observed that these values are below the midpoint of the scale (< 3).Anxiety and psychosomatic symptoms were statistically higher in females than in males. This result is supported by some previous studies in Gaza (Abadsa & Thabet, 2012), Turkey (Bayram (Dyrbye, Thomas, & Shanafelt, 2006), U.S.A (Jenkins et al, 2013;Rosenthal & Schreiner, 2000;Ryba & Hopko, 2012). In Palestine, being an Arabic country, females get used to stay close with their mothers almost all the time since childhood.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It can be observed that these values are below the midpoint of the scale (< 3).Anxiety and psychosomatic symptoms were statistically higher in females than in males. This result is supported by some previous studies in Gaza (Abadsa & Thabet, 2012), Turkey (Bayram (Dyrbye, Thomas, & Shanafelt, 2006), U.S.A (Jenkins et al, 2013;Rosenthal & Schreiner, 2000;Ryba & Hopko, 2012). In Palestine, being an Arabic country, females get used to stay close with their mothers almost all the time since childhood.…”
Section: Resultssupporting
confidence: 82%
“…Several studies suggest high rates depression and anxiety, among university students all over the world and especially in Turkey (Bayram, 2008;Chia & Graves, 2016;Daniel, 2013;Jenkins, 2013;Ovuga, Boardman, & Wasserman, 2006;Wong et al, 2006), 8% of university students had depressive feelings in Jordan (HamdanMansour & Marmash, 2007), 75% of the university students had some degree of depressive symptoms in Jordan (Hamdan-Mansour et al, 2009). 27.5% of students had depressive symptoms and anxiety in Hong Kong (Wong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign translations . Several articles using foreign translations of the PCL‐S were located in the literature, accompanied by various diverse psychometric evidence, including two in Norwegian (Blix, Bang Hansen, Skogbrott Birkeland, Nissen, & Heir, ; Hem, Hussain, Wentzel‐Larsen, & Heir, ), two in French (Dubosc et al, ; Ventureyra, Yao, Cottraux, Note, & De Mey‐Guillard, ), and three in Chinese (Erbes, Meis, Polusny, & Compton, ; Jenkins, Belanger, Connally, Boals, & Durón, ; L. Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Gerber, Boals, & Schuettler, ; Jenkins et al, ) analyzed gender disaggregated means and standard deviations (863 men and 1,800 women). The mean and standard deviation for men ( M = 26.03, SD = 12.32) is lower than the mean and standard deviation of women ( M = 29.28, SD = 13.42).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of our respondents were white and from college-educated US households—the demographic group most likely to have access to resources that allowed them to succeed at the highest levels of education [15,17,52]. Yet, the transition from graduate school to permanent employment is precarious, especially for women [17,53].…”
Section: Conclusion and Futurementioning
confidence: 99%